Changes in canopy structure and ant assemblages affect soil ecosystem variables as a foundation species declines. Issue 5 (12th May 2015) - Kendrick, Joseph A.; Ribbons, Relena R.; Classen, Aimée T.; Ellison, Aaron M.
Abstract : The decline of Tsuga canadensis (eastern hemlock)—a foundation tree species—due to infestation by Adelges tsugae (hemlock woolly adelgid) or its complete removal from a stand by salvage logging dramatically affects associated faunal assemblages. Among these assemblages, species composition (richness and abundance) of ants increases rapidly as T. canadensis is lost from the stands. Because ants live and forage at the litter‐soil interface, we hypothesized that environmental changes caused by hemlock loss (e.g., increased light and warmth at the forest floor, increased soil pH) and shifts in ant species composition would interact to alter soil ecosystem variables. In the Harvard Forest Hemlock Removal Experiment (HF‐HeRE), established in 2003, T. canadensis in large plots were killed in place or logged and removed to mimic adelgid infestation or salvage harvesting, respectively. In 2006, we built ant exclosure subplots within all of the canopy manipulation plots to examine direct and interactive effects of canopy change and ant assemblage composition on soil and litter variables. Throughout HF‐HeRE, T. canadensis was colonized by the adelgid in 2009, and the infested trees are now declining. The experimental removal of T. canadensis from the canopy was associated with an increase in the rate of cellulose decomposition by >50%, and exclosure of ants from subplots directly reduced their soil nitrate availability by 56%. Partial least squares path models revealed sequential interactive effects prior to adelgid infestation: canopy change (as a proxy for associated environmental changes) altered both decomposition and ant assemblage structure; changes in ant assemblage structure and decomposition rates altered nitrogen availability. The results illustrate that biotic changes directly associated with decline of T. canadensis can have cascading effects on ecosystem nutrient availability and cycling.